2006
DOI: 10.5271/sjweh.992
|View full text |Cite
|
Sign up to set email alerts
|

Preventing injury, illness and disability at work

Abstract: This discussion paper is intended to start a dialogue about prevention among those who are interested in making workplaces safer and healthier. The following four key themes are presented to build a framework for further discussion and activity: theme 1 -with multiple causes for workplace injury, illness, and disability, preventing these problems requires multiple solutions, operating in synergy; theme 2 -efforts to reduce workplace injury, illness, and disability must build on both primary and secondary preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 31 publications
(27 reference statements)
0
8
0
5
Order By: Relevance
“…Frank and Cullen have characterized active absence or return-to-work management as secondary prevention, which occurs after illness or disability has occurred and aims at reducing long-term disability [22]. Disability research suggests, however, that the retention of chronically ill workers requires a more pro-active approach, combining secondary prevention with primary prevention [23-27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frank and Cullen have characterized active absence or return-to-work management as secondary prevention, which occurs after illness or disability has occurred and aims at reducing long-term disability [22]. Disability research suggests, however, that the retention of chronically ill workers requires a more pro-active approach, combining secondary prevention with primary prevention [23-27].…”
Section: Introductionmentioning
confidence: 99%
“…According to Frank and Cullen, "primary prevention aims at reducing the risk of injury or illness before the absence occurs (while the person is still healthy). This aim is generally accomplished by modifying factors known to increase the risk of work disability by directly controlling a specific hazard or set of hazards, for example by increasing a worker's skills or modifying the work environment" [22]. …”
Section: Introductionmentioning
confidence: 99%
“…However, even in cases when adequate research exists, full application of such knowledge may be limited. That is, in our work with stakeholders, a common difficulty voiced by these partners was their own lack of knowledge about how to identify high quality research, and subsequently, how to translate available best-evidence research into useful information intended to inform policy, training and practice [9][10][11][12][13][14][15][16]. Despite their motivation to learn from current research, stakeholders often found the literature challenging to translate into practical solutions that could be meaningfully applied within the workplace.…”
Section: Introductionmentioning
confidence: 99%
“…Nesse caso, a promoção do retorno ao trabalho sustentável depende da integração de ações de assistência e vigilância da saúde dos trabalhadores. Frank 26 enfatiza essas ações de prevenção da incapacidade em vários níveis e propõe estratégias diversificadas, similares à proposta do modelo lógico do PRT. Outros estudos comprovam a importância da coordenação e sensibilização entre os atores sociais durante todo o processo de RT 8,12 .…”
Section: Sobre Os Resultados E Impactos Esperados Do Programaunclassified